Prevalence and purposes of gadget use among medical students - Lunge, Vasant Ramraoji; Kokiwar, P. R. (International Journal Of Community Medicine And Public Health, 2019)
Background: The prevalence of gadgets is increasing among the medical students and this is the matter to worry as they use it for other purposes than the science. Data need to focus on how many proportion of medical students use the gadgets and for what they use it. The objective was to study the prevalence and purposes of gadget use among medical students. Methods: An institution based cross-sectional study was carried out in among 306 medical students. This study was based on self-administered questionnaires. The whole batch of students was contacted on a particular day for data collection. Study questionnaires were distributed to them. In between, the doubts regarding any questions were clarified. The questionnaires were taken back after a half hour. An attempt was made to see that all the questions were completely responded to. The data was analyzed using proportions and mean values. Statistical tests like Chi-Square test, and Student’s T-test was used. Results: Majority of people using gadgets were female (71%). More than half of users were in the age group of 21-23 years. Smartphone was the most commonly used gadget. About 2/5th of the students used gadgets for about 1-3 hours. More than half of the students used gadgets in the sitting position. The vast majority of students used gadgets at chest level. Conclusions: The findings of this study indicate that use of gadgets takes a prevalent part in the daily lives of medical students.